Energy saving in a hurry: A research agenda and guidelines to study European responses to the 2022–2023 energy crisis. (March 2023) - Parag, Yael; Fawcett, Tina; Hampton, Sam; Eyre, Nick
Abstract: This winter exceptionally high energy prices are forcing many householders and businesses in Europe to change the way they use energy. It is important to learn how their energy use changes over a short period of time, the effects of government actions, which policies work and which fail, and what trade-offs emerge. The digital society offers unique opportunities to collect quantitative and qualitative data and to learn about these changes while they happen. However, researchers are not used to planning and executing rapid research. We propose a research agenda and some guidelines and thoughts on practical aspects of executing research in a hurry. The frequency of energy shortages due to extreme weather events is likely to increase. Therefore, lessons from good research on coping strategies, and on the economic, social, and environmental implications of this are vital for better policymaking. As researchers, we should try to follow Winston Churchill's advice 'never to waste a good crisis'.